An agricultural sector models for regional policy analysis and strategic planning - Pranevičius, Henrikas; Kurlavičius, Algimantas (Journal of Business Economics and Management, 2003)
The integration of Lithuania into the European Union requires serious preparation, determining possible changes in agrarian sector and rural development and their consequences, ensuring the necessary information supply to finding and substantiation of rational strategic solutions. The paper analyzes trends of systematic analysis of the agrarian sector of the region, tools for the search of solutions, reveals the possibilities of modelling methods and information technologies application in determining the sustainable development strategy. The suggested methodic of integrated modelling of agricultural production processes in regional and farm level is introduced. The scheme of agrarian production system and some functional dependencies are presented. The problems that are expected to be solved in future are formulated.First Published Online: 14 Oct 2010